On the Optimal Size of a Buffer Stock -The Case of Wheat in Pakistan (The Pakistan Development Review, 1985)
In a study of the operation of the wheat market in Pakistan, Cornelisse and Naqvi [I, p. 116] stated that the pre-harvest wheat stock in March 1983 of 2,100,000 tons should provide sufficient protection against a major harvest failure. This conclusion was based on the observation that a stock of that size corresponded to approximately 40 percent of the marketed surplus of wheat and to 17 percent of domestic production - very secure proportions according to the prevailing standards. Two questions, however, remain. One, it is not yet clear what the chances are that a bad harvest or a series of bad harvests wipes out the available stock and - if that happens - what is the expected volume of wheat imports needed to supplement the stock. Two, while security is one concern in buffer stock management, the cost aspect is another. A large buffer stock provides excellent security, but it also entails high costs of storage; a smaller stock may reduce security only slightly and reduce costs considerably. On the other hand, if a buffer stock is small, the probability that supplementary imports are needed is relatively high and so is the expected volume of these imports. Considering the fact that in Pakistan domestically produced wheat is much cheaper than imported wheat, this implies that a small stock of wheat, too, may involve high costs, in this case due to imports. Thus the question arises: what is the size of the wheat buffer stock that minimizes costs?